On Removing a Trump Card: Flesh and Blood and the Reign of God - Johnson, Clinton Andrew (Bulletin for biblical research, 2003)
This article reexamines the meaning of the phrase "flesh and blood" in 1 Cor 15:50 in light of two recent proposals (Martin, Asher) as to the reason why "some" in Paul's audience are denying a future resurrection. While assuming these nuanced proposals cogently describe the assumptions of Paul's audience, the article contends that Paul does not use "flesh and blood" to denote the particular "stuff" of which human beings are composed. Hence, contra these recent proposals, 1 Cor 15:50 does not exclude the possibility that the fleshly "stuff" of the human person is able to be redeemed/transformed and yet remain fleshly material capable of participating as such in the coming kingdom of God.